Cold shock protein a from Corynebacterium pseudotuberculosis: Role of electrostatic forces in the stability of the secondary structure - Coronado, Monika A. [UNESP]; Caruso, Icaro P. [UNESP]; De Oliveira, Vinícius M. [UNESP]; Contessoto, Vinícius G. [UNESP]; Leite, Vitor B.P. [UNESP]; Kawai, Liege A. [UNESP]; Arni, Raghuvir K. [UNESP]; Eberle, Raphael J. [UNESP] (Bentham Science Publishers, 2017)
The conformational stability of the Cold shock protein A (CspA) from C. pseudotuberculosis (Cp), a nucleic acid binding protein in function of pH and salt concentration was examined by using differential scanning calorimetry and CD spectroscopy in combination with computational analysis to identify the specify amino acids undergoing change. Our approach identified a sodiumbinding site in CpCspA and at pH 8.0 a significant reduction in the β-sheet content was observed which resulted in a decrease of the protein thermal stability. The computational analyses identified His30 and His65 as the amino acids with the largest charge shifts at different pHs. His30/His65 are part of the extensive hydrogen bonding network and along with the ion-binding site are essential for the conformational stability of CspA.
Keywords: C. pseudotuberculosis; Cold shock protein; Histidine; Ion binding; PH; Secondary structure